Design and Build Pedestrian Lane Automatic Vehicle Restraint System: Solutions to Make It Easier for Road Crossers - Syah, Angga David Maolana; Istiyanto, Bambang; An Najwa, Dihya; Ariffansyah, Yunindra Eka (Fidelity : Jurnal Teknik Elektro, 2025)
The problem that is often faced in the crossing area is the lack of safety for pedestrians due to the absence of automatic vehicle protective equipment. Without a system that can automatically hold or slow down the vehicle, drivers are less likely to reduce their speed when approaching the crosswalk, increasing the risk of accidents and making it difficult for pedestrians to cross safely. In this study, the variables used are dependent variables or bound variables. Explain the effectiveness of vehicle restraint, pedestrian safety level, driver reaction time and system success percentage. The method in this study is experimental, namely by manipulating pedestrians with tools. At the same time regarding the overview of the principles or process of the tool. The design of this system is expected to be an innovative solution to make it easier for pedestrians, reduce the risk of accidents in crossing areas and make a positive contribution to improving road safety.